The Pointsman: Maxwell’s Demon, Victorian Free Will, and the Boundaries of Science - Stanley, Matthew (Journal of the history of ideas, 2008)
This article discusses the writings of the devout Christian physicist James Clerk Maxwell (best known for his epochal work in electromagnetism and statistical mechanics) on the concept of conscious free-will. To Maxwell a correct understanding of free will, as personified in the example of the railway pointsman, was essential to clear conceptions of both man as a religious creature and of the limits of science. Understanding human volition, then, was not an end unto itself. It was a foundation on which one could build reliable theories of man and matter.